2003
DOI: 10.1034/j.1600-051x.2003.300108.x
|View full text |Cite
|
Sign up to set email alerts
|

A split‐mouth study on periodontal and microbial parameters in children with complete unilateral cleft lip and palate

Abstract: These data indicate that the periodontium in UCLP patients can cope well with a long-term orthodontic treatment, even in unfavourable conditions (like absence of attached gingiva and poor oral hygiene).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 32 publications
7
38
0
16
Order By: Relevance
“…9,11,12 These findings suggested the presence of a long connective tissue attachment in the cleft regions. 12 The results of these studies are consistent with the report of Quirynen et al 2 that teeth in the cleft had significantly more bone loss compared with contralateral noncleft control teeth. However, approximal probing depth and attachment loss values were also significantly higher than for contralateral teeth.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…9,11,12 These findings suggested the presence of a long connective tissue attachment in the cleft regions. 12 The results of these studies are consistent with the report of Quirynen et al 2 that teeth in the cleft had significantly more bone loss compared with contralateral noncleft control teeth. However, approximal probing depth and attachment loss values were also significantly higher than for contralateral teeth.…”
Section: Introductionsupporting
confidence: 83%
“…2,9,11,12,16 Bragger et al 12 reported that radiographic alveolar bone loss was greater at a cleft site compared with controls, despite a similar clinical attachment level. This suggested the presence of a periodontal attachment apparatus characterized by the presence of a long supracrestal connective tissue attachment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations